Workload Measures - Gawron, Valerie J., author (Boca Raton, FL : CRC Press/Taylor & Francis Group, 2019)
"This book was developed to help researchers and practitioners select measures to be used in the evaluation of human/machine systems. The book includes definitions of human workload and situational awareness and a review of measures. Each measure is described, along with its strengths and limitations, data requirements, threshold values, and sources of further information. To make this reference easier to use, an extensive author and subject indices are provided".